Portugal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Portugal reviews the considerations regarding productivity slowdown. The favorable evolution of income growth from the 1970s to the mid-1990s in Portugal was associated with above-average productivity growth but also reflected a more moderate decline in the amount of hours worked than that experienced in other countries in Europe. Portugal was an outstanding performer with double-digit productivity increases in large several high-tech industries. The evidence suggests that the negative impact of high labor adjustment costs on productivity is more intense for small- and medium-size companies and depends on the nature of wage-bargaining systems.